The Formulation of tourism industry and creative economy competitiveness index of provinces in Indonesia - Uswatun Nurul Afifah; Endan Suwandana; Eni Lestariningsih (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study proposes and calculates a new index called the Tourism and Creative Economy Industry Competitiveness (TCEIC) Index or Parekraf Index which aims to determine the description of the tourism industry and creative economy of each province In Indonesia. The index is then applied to investigate the Covid-19 pandemic effects and can be used for future planning and evaluating the involved parties in tourism sectors. The data used in this research is secondary data sourced from the publication of Tourism Industry Statistics and Creative Economy 2020 which is produced by a collaboration between the Ministry of Tourism and Creative Economy and the BPS-Statistics in 2021. Factor analysis was used to compile the index, following the Organisation for Economic Co-operation and Development (OECD). The implementation of the new Parekraf index to the 2020 pandemic data found that several provinces had very low scores, i.e. Sumatera and Sulawesi. This means that the central government should synergize with local governments in those areas and should be more sensitive and responsive to the tourism industry and the creative economy, especially on indicators that have a significant impact.